Novos rumos, velhos hábitos: debates acerca do trabalhador rural na Assembléia Nacional Constituinte Portuguesa de 1911 - Russo, Renan Henrique Oliveira [UNESP] (2015)
Portugal, in 1911, was in the midst of a turbulent political change. The newly installed Republican government was intended to be democratic, supporter of universal suffrage and solver of the labor crisis in the country. However, some practices were not consistent with the theory. The reflections came in the National Constituent Assembly of 1911. We believe that by analyzing the institution that legislated on the directions of Republic, it should be founded discussions that included the country‟s majoriarian professional class: rural workers. We stress that expect a stronger stance, on the part of politicians, to the causes of that class is not anachronism. Authors like Leon Poinsard, Basílio Teles, José Picão and other contemporaries, already indicated the best use of these classes as the key to the national economy, since they were the main source of export country, as well as basis for other industries. It is on this issue that focuses this work.